2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944942
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on quantitative assessment of muscle imbalance: Differences of muscle synergies, equilibrium-point trajectories, and endpoint stiffness in normal and pathological upper-limb movements

Abstract: This paper proposes a novel method for assessment of muscle imbalance based on muscle synergy hypothesis and equilibrium point (EP) hypothesis of motor control. We explain in detail the method for extracting muscle synergies under the concept of agonist-antagonist (AA) muscle pairs and for estimating EP trajectories and endpoint stiffness of human upper limbs in a horizontal plane using an electromyogram. The results of applying this method to the reaching movement of one normal subject and one hemiplegic subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The physics-based approach is a powerful way to reverse engineer the control mechanism underlying the neuromusculoskeletal system in the dynamic environment. For more details on muscle synergies based on the AA concept, refer also to our recent publications (Koba et al, 2014 ; Oku et al, 2014 , 2015 ; Uno et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The physics-based approach is a powerful way to reverse engineer the control mechanism underlying the neuromusculoskeletal system in the dynamic environment. For more details on muscle synergies based on the AA concept, refer also to our recent publications (Koba et al, 2014 ; Oku et al, 2014 , 2015 ; Uno et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that muscle activities during upper limb reaching movements by healthy subjects are represented by three invariant functional synergies [9]. Moreover, the muscle synergies and endpoint stiffness of the reaching movement in a post-stroke subject were different from those of a healthy subject [10]. However, the examined motor tasks were limited to simple reaching movements, and our muscle synergy analysis has not been validated by comparison with conventional mechanical perturbation method in post-stroke subjects.…”
Section: Introductionmentioning
confidence: 89%
“…The physics-based approach is a powerful way to reverse engineer the control mechanism underlying the neuromusculoskeletal system in the dynamic environment. For more details on muscle synergies based on the AA concept, refer also to our recent publications (Koba et al, 2014;Oku et al, 2014Oku et al, , 2015Uno et al, 2014).…”
Section: Physics-based Approach To Muscle-synergy Extractionmentioning
confidence: 99%